Accounting for business combinations (Advanced Accounting 2) - Millan, Zeus Vernon B. (Baguio City : Bandolin Enterprise, 2021)
This book is intended for students taking up the CHED required subject Accounting for business combinations. This book is based on current Philippine financial reporting standards.
1. Current liabilities -- 2. Notes payable -- 3. Bonds payable and other concepts -- 4. Provisions, contingent liabilities and contingent asset -- 5. Employee benefits (part 1) -- 6. Employee benefits (part 2) -- 7. Leases (part 1) -- 8. Leases (part 2) -- 9. Income taxes -- 10. Shareholders' equity (part 1) -- 11. Shareholders' equity (part 2) -- 12. Share-based payments (part 1) -- 13. Share-based payments (part 2) -- 14. Book value per share -- 15. Earnings per share.
Includes bibliographical references.
Keywords: ACCOUNTING